Indonesia-Japan Cooperation During Covid-19 - Setiawan, Filzah Nazurah; Siagian, Sagita Natasya (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
The outbreak of the Covid-19 pandemic, caused by the SARS-CoV-2 virus from the coronavirus family responsible for SARS and MERS, originated in Wuhan and quickly spread globally. International collaboration has been pivotal in the fight to achieve endemic control. Every nation has strived to acquire Covid-19 vaccines to safeguard their populations. For example, Indonesia forged a bilateral partnership with Japan to secure Covid-19 vaccines. Japan holds a strategic position as one of Indonesia's top five investors. Throughout the pandemic, the Indonesian Ministry of Foreign Affairs maintained close communication with its Japanese counterpart to request support in obtaining the Covid-19 vaccine. This collaboration was made possible by Indonesia's independent and proactive foreign policy, which created extensive opportunities for cooperation during the pandemic. This study aims to present the outcomes of the Indonesia-Japan collaboration in procuring Covid-19 vaccines for Indonesia, showcasing the implementation of an independent and proactive foreign policy that can yield substantial benefits.